An investigation of performer embodiment and performative interaction on an augmented stage - Brown, Richard (2019)
This thesis concerns itself with an investigation of live performance on an augmented stage in front of an audience, where performers witness themselves as projection mapped virtual characters able to interact with projected virtual scenography. An interactive virtual character is projected onto the body of a performer, its movements congruent with the performer. Through visual feedback via a Head Mounted Display (HMD), the performer is virtually embodied in that they witness their virtualised body interacting with the virtual scenery and props of the augmented stage.